Extension education principles through postgraduate programme: A Conceptual Review - Yusof, Atikah; Arshad, Mohd Mursyid; Hamzah, Siti Rabaah (Human Resource Management Academic Research Society (HRMARS), 2023)
Through the incorporation of self-directed learning and remote learning into the educational system, the sequence from the diffusion of COVID-19 and the transition to the endemic phase has resulted in an awareness of lifelong learning. In light of the fact that self-efficacy in the learning process is the foundation of Positive Youth Development (PYD), e-learning has become the most popular choice and continues to be used. As a consequence, there is a need to improve self-efficacy in the learning process. In the context of education, self-efficacy is a significant factor in determining student accomplishment throughout the learning process and a contributor to the development of generic skill. The learning process can be fulfilled through obtaining formal education through the university system, with a focus on the Extension Education as a hub for the process of lifelong learning. Exploration of the Extension Education serves as the basis for the viability of postgraduate programmes, giving people the chance to acquire balanced skill sets while also helping them to attain their goals. Thus, the intention of this concept paper will thoroughly explain the definition and development of Extension of Education and how the postgraduate course complies to the parameters set out in the area of extension education and how this process of learning impacts the Positive Youth Development. In this study, generics are viewed as a vital element that must be integrated into each person's life in order for them to live a lifelong life, in addition to being seen as a strength to meet obstacles in the world of work. It must begin by examining how a formal education system fosters the growth of self-efficacy. Youth empowerment during this time period depends on the process of applying skills in a real-world environment since it promotes the concept of responsibility and the perception that their efforts are having a positive impact. The elements of the ‘5C’ in Positive Youth Development will be nurtured during this process through effective youth-adult connection throughout the skill-building activities, as well as youth engagement and leadership.